ChatGPT and Ijtihad in Shariah Economic Law - Nugroho, Bramantyo Suryo; Rosyadi, Imron; Isman, I (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
ChatGPT, as an AI representation, can understand human language and provide responses simulating human interactions. In the context of Islamic law, this technology can assist scholars in interpreting Shariah economic laws by processing information from primary sources such as the Quran, Hadith, and Islamic literature. However, the use of ChatGPT in ijtihad for Shariah economic law poses complex challenges. This technology has limitations in understanding the context of Islamic legal principles and the nuanced language crucial for interpreting Islamic law. Additionally, ethical aspects are crucial, particularly in issuing fatwas or ijtihad related to Shariah Economic Law. This research aims to explain the concept of ijtihad from the perspective of Islamic law and address whether ChatGPT can act as a giver of fatwas in the aspect of Shariah Economic Law. This research employs a descriptive qualitative approach with a normative phenomenological approach. Primary data is gathered from literature sources and references on Islamic law, while secondary data is obtained from ChatGPT responses to the given prompts. The research concludes that ChatGPT, as a technological advancement, offers an ijtihad model that transcends time. However, ChatGPT has not yet been capable of being utilized as a giver of fatwas in the aspect of Shariah Economic Law. This is due to: (a) ChatGPT's difficulty in recognizing and comprehending words with specific and profound contexts, and (b) input data sourced from big data cannot guarantee the authenticity of the data when used for making legal decisions, particularly in Shariah Economic Law. There has not been a detailed study discussing ChatGPT as a means of ijtihad, specifically as a provider of fatwas in the domain of Shariah Economic Law.